Application of zeolite adsorption and biological anaerobic digestion technology on hydrothermal liquefaction wastewater - Ruirui, Li; Xia, Ran; Na, Duan; Zhang, Yuanhui; Zhidan, Liu; Haifeng, Lu (International Journal of Agricultural and Biological Engineering, 2017)
The post-hydrothermal liquefaction wastewater (PHWW) was obtained from a conversion process of Spirulina sp. to bio-crude oil via hydrothermal liquefaction (HTL) technology that was rich in organic matter and toxicant. In this study, zeolite was applied to overcome the inhibitions and improve anaerobic digestion (AD) efficiency. Three zeolite adding ways were evaluated: PHWW pretreated with zeolite for 5 h with/without solid-liquid separation before AD process and zeolite added to PHWW AD process directly, in order to find the most ideal way to add zeolite. Results indicated that zeolite had a positive effect on the AD process of the PHWW. The gas potential of PHWW after adding zeolite, as well as the chemical oxygen demand (COD) removal rate, was much higher than those of its initial state. Especially when the PHWW was pretreated by zeolite for 5 h without separation, the biogas yield increased by 73.96% (6170 μmol/g CODremoved) compared with the initial PHWW (3546.7 μmol/g CODremoved).Keywords: post-hydrothermal liquefaction wastewater, anaerobic digestion, zeolite adsorption, biogasDOI: 10.3965/j.ijabe.20171001.2704Citation: Li R R, Ran X, Duan N, Zhang Y H, Liu Z D, Lu H F. Application of zeolite adsorption and biological anaerobic digestion technology on hydrothermal liquefaction wastewater. Int J Agric & Biol Eng, 2017; 10(1): 163–168.